Chapter Dingen die ertoe doen! - Bosch, Mineke (Amsterdam University Press, 2023)
In this contribution Mineke Bosch connects to Rosemarie Buikema's work with the Museum of Equality and Difference which aims at inspiring museum and exhibition curators to tell more complex stories that include postcolonial and gender perspectives. Bosch focuses on the importance of objects for the history of women and gender, and the value of historical knowledge about women and gender for museums and heritage institutions. She does so by discussing many aspects of the making of the exhibition Strĳd! 100 jaar vrouwenkiesrecht (Struggle! 100 Years of Women's Suffrage) in the Groninger Museum in 2019. The exhibition through its objects not only changed the story of women's suffrage, it also enlarged 'suffrage literacy'. This in turn led to the recognition and acceptance of objects from this historical episode by museums.